Double-color display pressure sensing adhesive tape
By adopting the design and optimization process of double color display in the pressure sensing tape, the problems of insufficient pressure response range, contrast, response speed and durability in the prior art are solved, and more efficient and durable pressure sensing performance is achieved.
Patent Information
- Application Number
- CN202411937073.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
Existing pressure sensing products have shortcomings in pressure response range, color display contrast, response speed and durability, which are difficult to meet diverse application needs.
Double-color display pressure sensing tape, including a flexible bottom layer, a pressure-sensitive functional layer and an optically enhanced surface layer. The pressure sensing functional layer consists of piezoelectric crystal particles, rare earth oxide particles, conductive fillers, dispersants and crosslinkers. Through optimized design and preparation processes, the pressure sensing performance is significantly improved.
It significantly improves the sensitivity and contrast of pressure sensing, shortens the color recovery time, enhances durability and mechanical properties, adapts to a wider range of usage scenarios, and meets modern and multifunctional needs.
Smart Images

Figure CN119709040A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive tapes, and in particular relates to a dual-color display pressure-sensitive adhesive tape. Background Art
[0002] In the fields of modern industry, medical treatment and consumer electronics, pressure sensing technology has been widely used as an important detection method. At present, pressure sensing tapes or films usually use optical or electrical means to achieve pressure detection and display. Its application scenarios include medical monitoring, packaging pressure detection, industrial sealing pressure uniformity evaluation, etc. However, the existing technology has the following shortcomings in actual use:
[0003] Limited pressure response range: Most existing pressure sensing products can only display within a specific pressure range (such as a single range of low pressure or high pressure), and it is difficult to cover a wide range from small pressure to large pressure. This limitation makes it unable to meet the needs in a variety of application scenarios.
[0004] Insufficient color display contrast: Existing pressure sensing products based on optical display are often affected by ambient light, and the color display contrast is low, especially in low-light environments or complex backgrounds. It is difficult to clearly identify color changes, affecting the actual use effect.
[0005] Slow response speed: After pressure is applied or released, the time it takes for the color to recover to its initial state in the prior art is usually long (generally more than 10 seconds), which is not suitable for application scenarios that require fast dynamic response, such as real-time pressure monitoring or dynamic load analysis.
[0006] It is difficult to strike a balance between flexibility and mechanical performance: some pressure-sensitive films or tapes are susceptible to deformation when used on complex surfaces, causing the pressure-sensitive layer to separate from the underlying material and failing to provide reliable pressure sensing. In addition, it is often difficult to strike a balance between flexibility and mechanical strength, limiting the durability and service life of the product.
[0007] Uneven pressure distribution display: Under irregular surfaces or complex contact conditions, the material distribution and particle uniformity of the pressure-sensitive layer in the prior art are insufficient, resulting in inaccurate pressure display or local failure, affecting the actual detection effect.
[0008] Lack of versatility: Most existing pressure sensing products only support optical display and lack the ability to interact with smart devices or multi-modal sensing (such as electrical signal output, tactile feedback), making it difficult to meet application scenarios with modern and multi-functional requirements.
[0009] Insufficient durability and reliability: After multiple cycles of pressure loading, existing pressure-sensitive tapes or films often experience performance degradation or failure, affecting their long-term stability and increasing maintenance and replacement costs.
[0010] The preparation process is complex and the cost is high: Some existing technologies rely on complex manufacturing processes, such as multi-step coating, high-precision thin film preparation, etc., which not only increases the production difficulty, but also increases the manufacturing cost, limiting its large-scale promotion.
[0011] In response to the above problems, the existing technology urgently needs a pressure-sensing tape that can achieve a wider pressure response range, higher display contrast, faster response speed and higher durability, while simplifying the preparation process, reducing manufacturing costs, and meeting the diverse application needs in the medical, industrial, logistics and consumer fields. Summary of the invention
[0012] The purpose of the present invention is: The present invention aims to provide a dual-color display pressure-sensitive tape, which not only solves the problems of insufficient sensitivity, low contrast, slow response speed and poor durability in the prior art, but also significantly improves the pressure sensing performance and application adaptability through optimized design and preparation process, and has broad market application prospects.
[0013] The technical solution adopted by the present invention is as follows:
[0014] A dual-color display pressure-sensitive adhesive tape, comprising a bottom layer, a pressure-sensitive functional layer and a surface layer, wherein the bottom layer is a flexible substrate, which is composed of a polyethylene terephthalate substrate and a flexible material, wherein the polyethylene terephthalate substrate has a thickness of 25-125 μm, and the flexible material is selected from polydimethylsiloxane or thermoplastic polyurethane, and has a coating thickness of 30-100 μm, and is used to provide flexible support and conformability;
[0015] The pressure-sensitive functional layer is composed of an elastomer matrix, piezoelectric crystal particles, rare earth oxide particles, conductive fillers, dispersants and cross-linking agents; wherein:
[0016] The mass proportion of piezoelectric crystal particles is 20%-50%, and they are selected from barium titanate or sodium potassium niobate, which can induce light scattering effect through pressure and display the first color in the low pressure range;
[0017] The mass proportion of the rare earth oxide particles is 5%-15%, and they are selected from neodymium oxide or europium oxide, and can induce the shift of the light absorption peak by pressure, and display a second color in the high pressure range;
[0018] The conductive filler accounts for 1% to 5% by mass and is selected from graphene oxide or carbon nanotubes to enhance pressure transmission and response;
[0019] The mass proportion of the dispersant is 0.5%-2%, and it is selected from polyethylene glycol, polymethyl methacrylate or nonylphenol polyoxyethylene ether, and is used to improve the dispersion uniformity of the particles in the matrix;
[0020] The cross-linking agent accounts for 1% to 3% by weight and is selected from diisocyanate or peroxide, and is used to enhance the mechanical strength and stability of the base material;
[0021] The mass proportion of the elastomer matrix is 30%-70%, and is selected from polydimethylsiloxane or polyurethane;
[0022] The surface layer is an optical enhancement layer, which is made of transparent polycarbonate or polymethyl methacrylate, has a thickness of 10-50 μm, and is coated with a silicon oxide anti-reflective coating to enhance the optical display effect and protect the pressure-sensitive functional layer.
[0023] Preferably, the pressure-sensitive functional layer exhibits a bistable optical property within a pressure sensing range, wherein the response pressure of the first color is 0.01-1 kPa, and the response pressure of the second color is 1-100 kPa.
[0024] Preferably, the piezoelectric crystal particles and the rare earth oxide particles of the pressure-sensitive functional layer are mixed in a mass ratio of 3:1 to 5:1 to optimize the color conversion effects of low pressure and high pressure.
[0025] Preferably, after the pressure is released, the pressure-sensitive functional layer of the adhesive tape can restore the dual-color display to a transparent effect of a pressure-free state within 5 seconds.
[0026] A method for preparing the dual-color display pressure-sensitive adhesive tape comprises the following steps:
[0027] Step 1. Bottom layer preparation:
[0028] a. Dissolve polydimethylsiloxane or thermoplastic polyurethane in a matrix material to solvent mass ratio of 1:2 to 1:4, stirring at a speed of 200-500rpm for 20-40 minutes;
[0029] b. The solution is coated on a polyethylene terephthalate substrate using a blade coating or spin coating process, with a coating thickness of 30-100 μm;
[0030] c. Curing at 80-120°C for 20-40 minutes to form a flexible bottom layer;
[0031] Step 2. Preparation of pressure-sensitive functional layer:
[0032] a. adding piezoelectric crystal particles, rare earth oxide particles, conductive fillers and dispersants to the elastomer matrix material;
[0033] b. Stirring using a high-speed shear dispersion device at a stirring speed of 3000-5000rpm for 30-60 minutes, and performing ultrasonic dispersion at an ultrasonic frequency of 20-40kHz for 10-20 minutes;
[0034] c. Add a crosslinking agent and stir at 50-70°C for 60-90 minutes to form a uniform pressure-sensitive functional material;
[0035] d. Use roller coating or spray coating process to apply on the base layer with a coating thickness of 50-150μm;
[0036] e. Curing at 120-150°C for 30-60 minutes to form a pressure-sensitive functional layer;
[0037] Step 3. Surface preparation:
[0038] a. Using an extrusion molding process to make a transparent polycarbonate or polymethyl methacrylate film with a thickness of 10-50μm;
[0039] b. Spraying a silicon oxide anti-reflective coating on the surface of the film with a coating thickness of 50-200nm;
[0040] c. Curing at 120-180°C for 5-15 minutes to form an optical enhancement layer;
[0041] Step 4. Multi-layer composite:
[0042] a. Arrange in the order of bottom layer, pressure-sensitive functional layer and surface layer;
[0043] b. Use vacuum hot pressing process for multi-layer composite, the hot pressing temperature is 80-120℃, the pressure is 30-100MPa, and the time is 20-40 minutes;
[0044] Step 5. Cutting and shaping:
[0045] a. Use laser cutting equipment to cut to the predetermined size, the laser power is 15-30W, and the cutting speed is 5-20mm / s;
[0046] b. Trim the edges to ensure they are smooth and free of burrs.
[0047] Preferably, in the operation steps of the vacuum hot pressing process, the bottom layer and the surface layer are electrostatically cleaned before composite lamination to remove surface particles and improve composite quality.
[0048] Preferably, the dispersant is added in two steps: the first step is to add 50% of the dispersant before high-speed shear dispersion, and the second step is to add the remaining 50% of the dispersant before ultrasonic dispersion to further improve the dispersion uniformity of the particles.
[0049] The beneficial effects of the present invention are:
[0050] 1. Dual color display sensitivity is significantly improved
[0051] The existing technology can usually only cover a narrow pressure range and it is difficult to achieve accurate sensing of a wide pressure range. The present invention uses the synergistic effect of piezoelectric crystal particles and rare earth oxide particles to achieve dual-color display from low pressure to high pressure, significantly expanding the pressure sensing range and improving the sensitivity to tiny pressures.
[0052] 2. Color display contrast is significantly enhanced
[0053] In the prior art, in low-light environments or complex backgrounds, color display is easily disturbed by ambient light, resulting in insufficient contrast. The present invention introduces a silicon oxide anti-reflective coating on the surface layer and combines it with the optimized design of the particle spectral response to effectively improve the color display contrast and ensure clear identification under various light conditions.
[0054] 3. Faster color recovery
[0055] The existing technology takes a long time to restore color after pressure is released (generally > 10 seconds), which affects the continuity of real-time monitoring. The present invention optimizes the pressure-sensitive functional layer material (such as a high-efficiency elastic matrix and evenly dispersed functional particles) to achieve color restoration to a transparent state within 5 seconds after pressure is released, significantly improving the dynamic response performance.
[0056] 4. Improved uniformity of pressure distribution
[0057] When the existing technology is applied on complex surfaces, the pressure-sensitive layer is prone to insufficient local response. The present invention combines a flexible bottom layer with a highly dispersed pressure-sensitive material (a two-step dispersant addition process) to ensure that the pressure-sensitive functional layer is evenly stressed and improve the sensing accuracy of pressure distribution.
[0058] 5. Optimization of mechanical properties and flexibility
[0059] In the prior art, it is often difficult to balance the bonding strength and flexibility of the pressure-sensitive functional layer and the base material. The present invention provides excellent mechanical support and excellent flexible bonding performance through the composite design of the PET base and the flexible material, and is suitable for complex curved surfaces or dynamic load scenarios.
[0060] 6. Durability is significantly improved
[0061] In the prior art, the performance of the tape is prone to degradation after multiple cycles of pressure loading. The present invention introduces a cross-linking agent to form a high-strength three-dimensional cross-linked network, which increases its ability to withstand cyclic pressure to more than 3,000 times, significantly higher than the prior art.
[0062] 7. Multifunctional expansion potential
[0063] Most existing technologies are single optical responses. The present invention provides a basis for the electrical signal output function by adding conductive fillers (such as graphene oxide and carbon nanotubes). It has the potential for multi-modal pressure perception and intelligent linkage, and expands the application boundaries of traditional pressure sensing technology.
[0064] 8. Optimization and simplification of preparation process
[0065] The existing technology mostly adopts a complex multi-step process, which increases cost and time. The present invention adopts an integrated preparation process of two-step dispersion, roll coating / spray coating combination, and vacuum hot pressing, which not only improves production efficiency, but also ensures the uniformity and performance stability of the pressure-sensitive layer.
[0066] 9. Enhanced environmental adaptability and market potential
[0067] Compared with the existing technology, the present invention can adapt to a wider range of usage scenarios, such as low-light environments, complex backgrounds and dynamic load scenarios (such as medical monitoring, industrial inspection, logistics and transportation, etc.), demonstrating significant practicality and commercial value.
[0068] In general, the present invention not only solves the problems of insufficient sensitivity, low contrast, slow response speed and poor durability existing in the prior art, but also significantly improves the pressure sensing performance and application adaptability by optimizing the design and preparation process, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION
[0070] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0071] See also Figure 1 The present invention relates to a dual color display pressure sensitive adhesive tape, comprising a bottom layer, a pressure sensitive functional layer and a surface layer, wherein:
[0072] Bottom layer: The bottom layer is a flexible substrate, which is composed of a polyethylene terephthalate (PET) substrate and a flexible material: the thickness of the polyethylene terephthalate substrate is 25-125 μm;
[0073] The flexible material is selected from polydimethylsiloxane (PDMS) or thermoplastic polyurethane (TPU), and the coating thickness is 30-100 μm; this layer is used to provide flexible support and conformability to complex surfaces.
[0074] Pressure-sensitive functional layer: The pressure-sensitive functional layer is composed of an elastomer matrix, piezoelectric crystal particles, rare earth oxide particles, conductive fillers, dispersants and cross-linking agents:
[0075] Piezoelectric crystal particles (20%-50%, by mass): selected from barium titanate or sodium potassium niobate, used for light scattering under low pressure (0.01-1 kPa) to produce the first color;
[0076] Rare earth oxide particles (5%-15%, by mass): selected from neodymium oxide or europium oxide, used for shifting the light absorption peak under high pressure (1-100 kPa) to produce a second color;
[0077] Conductive filler (1%-5%, by mass): selected from graphene oxide or carbon nanotubes, used to enhance pressure signal transmission and response;
[0078] Dispersant (0.5%-2%, by mass): selected from polyethylene glycol (PEG), polymethyl methacrylate (PMMA) or nonylphenol polyoxyethylene ether, used to improve particle dispersion;
[0079] Cross-linking agent (1%-3%, by mass): selected from diisocyanate or peroxide, used to improve the mechanical strength and stability of the matrix;
[0080] Elastomer matrix (30%-70%, mass ratio): selected from polydimethylsiloxane or polyurethane.
[0081] surface layer:
[0082] The surface layer is an optical enhancement layer, which is made of transparent polycarbonate (PC) or polymethyl methacrylate (PMMA): the thickness is 10-50μm; the surface is coated with a silicon oxide anti-reflective coating (thickness 50-200nm) to enhance the optical display effect and protect the pressure-sensitive functional layer.
[0083] Preferred Features
[0084] The pressure-sensitive functional layer exhibits bistable optical properties within the pressure range:
[0085] The response pressure of the first color is 0.01-1kPa;
[0086] The second color responds to pressures of 1-100 kPa.
[0087] The piezoelectric crystal particles and the rare earth oxide particles of the pressure-sensitive functional layer are mixed in a mass ratio of 3:1 to 5:1 to optimize the color conversion effects of low pressure and high pressure.
[0088] After the pressure on the pressure-sensitive functional layer is released, the dual-color display can return to a transparent state without pressure within 5 seconds.
[0089] The preparation method of the adhesive tape is as follows:
[0090] Step 1: Base layer preparation
[0091] a. Dissolution of flexible materials:
[0092] Dissolve polydimethylsiloxane (PDMS) or thermoplastic polyurethane (TPU) at a mass ratio of 1:2 to 1:4 between the base material and the solvent. Stir at a speed of 200-500rpm for 20-40 minutes to ensure a uniform solution. Solvents (such as cyclohexanone, toluene, etc.) penetrate between polymer molecules through their polarity or intermolecular forces, breaking the hydrogen bonds or van der Waals forces between polymer chains. Among them, polar solvents (such as cyclohexanone) are more suitable for dissolving polyurethanes (TPU) with a certain polarity. Non-polar solvents (such as toluene) are more suitable for dissolving non-polar materials such as polydimethylsiloxane (PDMS). Stirring provides mechanical force to accelerate the dispersion of polymer molecules and evenly distribute them in the solvent. The stirring speed (200-500rpm) ensures that sufficient shear force can be provided while avoiding the formation of bubbles in the solution caused by high-speed stirring.
[0093] b. Coating and curing:
[0094] The solution is applied to the PET substrate using a doctor blade or spin coating process with a coating thickness of 30-100μm; cured at 80-120°C for 20-40 minutes to form a flexible bottom layer. Doctor blade / spin coating evenly distributes the material and controls the film thickness by surface tension and viscosity. Heating evaporates the solvent and rearranges the polymer molecules to form a continuous flexible film. This provides flexible support and improves the conformability and mechanical strength of the bottom layer.
[0095] Step 2: Preparation of pressure-sensitive functional layer
[0096] a. Mixing:
[0097] Piezoelectric crystal particles, rare earth oxide particles, conductive fillers, and dispersants are added to the elastomer matrix material according to the formula ratio; the dispersant is added in two steps: the first step is to add 50% before high-speed shear dispersion, and the second step is to add the remaining 50% before ultrasonic dispersion. The dispersant reduces the surface energy of the particles and forms a protective film on the surface of the particles to prevent particle agglomeration. The two-step addition method makes initial dispersion easier to complete, and subsequent enhanced dispersion further optimizes uniformity. The dispersant also improves the interfacial wettability between the particles and the elastomer matrix, allowing the particles to be evenly embedded in the elastomer. The shear force generated by high-speed stirring promotes uniform distribution of particles, laying the foundation for subsequent dispersion processes.
[0098] b. Dispersion:
[0099] Use high-speed shear dispersion equipment for stirring at a speed of 3000-5000rpm for 30-60 minutes; use ultrasonic dispersion treatment at an ultrasonic frequency of 20-40kHz for 10-20 minutes. The high-speed rotating blade applies strong mechanical shear force to the particles, breaking the agglomerated particles into smaller particles. The shear force distributes the particles more quickly and evenly into the elastomer matrix. Ultrasonic waves produce cavitation effects in liquids, exerting instantaneous impact force on the particles through the formation and bursting of tiny bubbles, further separating agglomerated particles. The high-frequency vibration of ultrasound can effectively disperse nano-sized particles (such as rare earth oxides and conductive fillers).
[0100] c. Cross-linking and coating:
[0101] Add a crosslinking agent (1%-3%), stir at 50-70°C for 60-90 minutes to form a uniform pressure-sensitive functional material; use a roller coating or spray coating process to coat the pressure-sensitive functional material on the bottom layer with a coating thickness of 50-150μm. Diisocyanate or peroxide crosslinkers form a three-dimensional crosslinked network through chemical reactions: diisocyanate reacts with hydroxyl or amino groups in the elastomer molecules to form a stable polyurethane network. Peroxide generates free radicals under heating conditions, initiating free radical crosslinking reactions of elastomer molecules. The crosslinking reaction increases the connection strength between molecular chains by forming chemical bonds, thereby improving the mechanical properties and thermal stability of the material. Roll coating applies the material through a uniformly rolling roller, and uses viscosity to control the film thickness. Spray coating uses a high-speed nozzle to atomize the material and evenly deposit it on the bottom layer surface, which is suitable for coating a thin and uniform pressure-sensitive layer. The pressure-sensitive functional material spreads on the bottom layer surface through intermolecular forces (such as surface tension and adhesion) to form a uniform film.
[0102] d.Cure:
[0103] Curing at 120-150℃ for 30-60 minutes forms a pressure-sensitive functional layer. The remaining cross-linking reaction during the curing process is further completed, strengthening the chemical bond between molecules. Thermal curing completely evaporates the residual solvent in the material to avoid bubbles or pores in the coating. Under the action of thermal energy, the elastomer molecular chains rearrange and form a stable structure, improving the density and mechanical strength of the material.
[0104] Step 3: Surface preparation
[0105] a. Extrusion molding:
[0106] Transparent polycarbonate (PC) or polymethyl methacrylate (PMMA) is made into a film with a thickness of 10-50 μm using an extrusion molding process. During the extrusion process, PC or PMMA particles melt at high temperatures (180-250°C), and the molecular chains relax under the action of thermal energy and enter a molten state.
[0107] Polycarbonate: It has a high glass transition temperature (about 150°C) and requires a higher temperature to melt.
[0108] Polymethyl methacrylate: The glass transition temperature is about 100°C and the processing temperature is relatively low.
[0109] The molten material is extruded through the die under the action of the screw. The shape and size of the die opening determine the thickness and uniformity of the film. The molecular flow is arranged along the die direction under high pressure, forming a uniform material flow.
[0110] The extruded molten material is rapidly cooled by the cooling roller, and the molecular chains are rearranged and solidified to form a film. The cooling rate determines the orientation of the molecular chains and the mechanical properties of the film. A higher cooling rate helps to form a film with better optical transparency.
[0111] b. Anti-reflective coating:
[0112] Spray a silicon oxide anti-reflection coating on the surface of the film with a coating thickness of 50-200nm; cure at 120-180℃ for 5-15 minutes to form an optical enhancement layer. The coating thickness is controlled by the sol concentration, spraying speed and nozzle pressure. The uniformity of the coating distribution depends on the number of spray coverage and the uniformity of the spray path.
[0113] Silicon oxide coating reduces light reflectivity through interference effect: when the coating thickness is 1 / 4 of the wavelength of light (λ / 4), the phase difference between the incident light and the reflected light is 180°, resulting in interference to eliminate reflection. The refractive index of silicon oxide (~1.46) is between air and PC / PMMA, which reduces interface reflection. For multilayer coatings, the superimposed interference effect further reduces reflectivity.
[0114] The curing temperature causes the solvent in the coating to evaporate quickly, forming a uniform coating. After the solvent molecules evaporate, the silicon oxide sol polymer molecules rearrange and solidify. The silicon oxide molecules complete the condensation reaction under the action of thermal energy to form a cross-linked structure. The formation of the SiO-Si network structure enhances the mechanical properties and durability of the coating. The curing process also improves the interfacial adhesion between the coating and the film surface. At high temperatures, the film surface molecules diffuse and cross-link with the coating molecules to improve the bonding strength.
[0115] Step 4: Multilayer Composite
[0116] a. Overlay arrangement:
[0117] The layers are stacked in the order of bottom layer, pressure-sensitive functional layer and surface layer. Each layer of material forms a preliminary bond through physical contact, where the matching of surface energy between materials ensures initial adhesion, and the pressure-sensitive functional layer and the flexible matrix of the bottom layer produce an interfacial wetting effect to enhance the bond. Before stacking, the bottom and surface layer surface particles are removed through an electrostatic cleaning process. Electrostatic cleaning uses a charged brush or electrostatic rod to eliminate surface particles and static charge to prevent impurities from hindering interlayer bonding.
[0118] During the arrangement process, each layer of material is controlled to be flat and wrinkle-free. The flexibility and moderate tension of the film material ensure that it can automatically adjust to fit the bottom layer when superimposed.
[0119] b. Vacuum hot pressing:
[0120] The vacuum hot pressing process is used for multi-layer composite, with a hot pressing temperature of 80-120°C, a pressure of 30-100MPa, and a time of 20-40 minutes. The vacuum environment effectively removes the air between the layers and prevents bubbles from remaining, thereby reducing the presence of air between the interfaces, preventing the material from stratification or bulging due to gas expansion caused by hot pressing, reducing the oxygen content, and reducing the impact of oxidation reactions at high temperatures on material properties.
[0121] The hot pressing temperature (80-120℃) is lower than the thermal deformation temperature of the base layer, functional layer and surface layer materials, but higher than the activation temperature of the cross-linking agent. Moderate heating can further improve the cross-linking structure in the pressure-sensitive functional layer and enhance the mechanical strength. The molecular chain movement of the surface layer and the pressure-sensitive functional layer is enhanced at high temperature, which increases the interface adhesion.
[0122] The hot pressing pressure (30-100MPa) makes each layer of material tightly bonded through mechanical force, and the high pressure makes the material interface fully fit, increasing the van der Waals force and mechanical intercalation between molecules. The pressure can also fill the tiny gaps formed by coating in the pressure-sensitive functional layer and improve the density between layers. The synergistic effect of heat and force forms a strong physical and chemical bond between materials. The bond between the bottom layer and the pressure-sensitive functional layer mainly depends on the entanglement and intercalation of molecular chains, and the bond between the surface layer and the pressure-sensitive functional layer forms interface adhesion through local molecular diffusion.
[0123] Step 5: Cutting into shape
[0124] a.Laser cutting:
[0125] Use laser cutting equipment to cut into predetermined size, laser power is 15-30W, cutting speed is 5-20mm / s.
[0126] b. Edge trimming:
[0127] Trim the cut edges to ensure they are smooth and free of burrs.
[0128] The pressure response mechanism of the dual color display of the present invention is:
[0129] 1. Low pressure range (0.01-1kPa): light scattering dominates
[0130] Under low pressure, the piezoelectric crystal particles undergo microstructural changes, the surface refractive index gradient increases, and light scattering is enhanced. The scattered light increases the intensity of a specific wavelength (such as 450-500nm, blue light), showing the first color. The light scattering effect is sensitive to external forces and responds quickly, making it suitable for color display with tiny pressures.
[0131] 2. High pressure range (1-100 kPa): light absorption dominates
[0132] Under high pressure, the crystal energy level distribution of rare earth oxide particles changes, and the wavelength of absorbed light shifts. The red shift or blue shift of the absorption peak reduces the transmission of light in a specific wavelength band (such as 620-680nm, red light), showing a second color. The light absorption peak shift provides a clear high-pressure range color display, which is suitable for sensing greater pressure.
[0133] The overall process of pressure sensing and color display of the present invention is as follows:
[0134] 1. Initial state:
[0135] When the tape is not under force, the piezoelectric crystal particles and rare earth oxide particles in the pressure-sensitive functional layer are in a natural state, the light scattering and absorption characteristics are not significant, and the entire tape appears transparent or in a default color.
[0136] 2. Apply pressure:
[0137] When external force is applied to the surface of the tape, the pressure is transmitted through the surface layer to the pressure-sensitive functional layer. Depending on the pressure, different mechanisms are activated:
[0138] Low pressure (0.01-1kPa): The surface refractive index of the piezoelectric crystal particles changes slightly, enhancing light scattering and showing the first color (such as blue).
[0139] High pressure (1-100kPa): The light absorption peak of rare earth oxide particles shifts, resulting in enhanced absorption of light in a specific band, showing a second color (such as red).
[0140] 3. Color change:
[0141] The color of the tape surface changes in real time due to the optical properties of the particles responding to external forces, and the display effect is optimized through anti-reflective coating to ensure that the color is clearly visible under different lighting conditions.
[0142] 4. Stress release and recovery:
[0143] After the external force is removed, the piezoelectric crystals and rare earth oxide particles restore their initial crystal structure, the optical properties return to the default state, and the color of the tape surface gradually returns to a transparent state (recovery time ≤ 5 seconds).
[0144] In addition, in order to solve the problem that the dual-color display pressure-sensitive tape has unclear color display in low-light environments or complex backgrounds with insufficient contrast, this paper proposes further improvement solutions:
[0145] Improvement plan 1: Particle surface treatment to optimize spectral response
[0146] A fluoride coating (such as barium fluoride) is introduced on the surface of barium titanate particles (particle size 0.5-1μm). The barium titanate particles are immersed in a 0.1mol / L barium fluoride solution, stirred for 30 minutes, dried and sintered at 300℃ for 2 hours. The band structure of the particles is fine-tuned, and the light scattering peak is moved to 450-500nm (blue light region).
[0147] Aluminum oxide film is coated on the surface of neodymium oxide particles (particle size 10-50nm). Using the sol-gel method, the neodymium oxide particles are mixed with aluminum salt solution, dried and calcined at 500℃ for 1 hour. The absorption peak is shifted to 630-680nm (red light region).
[0148] This increases the spectral response difference to above 180nm, significantly improving the color display contrast.
[0149] Improvement plan 2: Introducing a specific spectrum enhancement coating on the surface
[0150] Steps:
[0151] Add barium titanate nanoparticles to the surface anti-reflection coating, mix barium titanate particles (particle size 10-50nm) with anti-reflection coating materials (proportion 5%), apply by spraying, dry and solidify, so as to enhance the reflection intensity of 450-500nm blue light.
[0152] Rare earth europium oxide particles (particle size 10-30 nm) are added to the anti-reflection coating. The rare earth europium oxide particles are mixed with the anti-reflection coating material (proportion 5%), spray-coated, dried and cured, thereby enhancing the reflection intensity of 630-680 nm red light.
[0153] This increases the reflection intensity of blue light and red light by 30%-50% respectively, allowing for adaptation to complex backgrounds and low-light environments.
[0154] Improvement plan 3: Brightening fluorescent materials to enhance brightness in low-light environments
[0155] Steps:
[0156] Carbon nitride quantum dots (particle size 5-10 nm) were dissolved in ethanol, mixed with piezoelectric crystal particles at a ratio of 1%, ultrasonically dispersed for 30 minutes, and then dried, so that 450-500 nm blue light was emitted under the excitation of ultraviolet light (300-400 nm).
[0157] Manganese-doped zinc oxide particles (particle size 10-30nm) and rare earth oxide particles are mixed at a ratio of 1%, stirred evenly and added into the elastic matrix material, so that 630-680nm red light is emitted under the excitation of ultraviolet light (300-400nm).
[0158] This increases the brightness of the display area in low-light environments by more than 50%, enhancing the visibility of color display.
[0159] These improvements have the following effects:
[0160] 1. Improved color display contrast
[0161] The difference in spectral response between blue light and red light is expanded to above 180nm to avoid wavelength overlap.
[0162] The spectrum enhancement coating on the surface increases the reflection intensity of blue and red light, improving the contrast by 30%-50%.
[0163] 2. Adapt to low light environments
[0164] Brightness-enhancing fluorescent materials significantly enhance display brightness in low-light environments, making colors clearly visible in low-light conditions.
[0165] In this example, adhesive tapes were prepared and tested within the formulation and process ranges, and the results are summarized as follows:
[0166] Among them, test parameters and prerequisites
[0167] Base layer thickness: different thicknesses (50-125 μm) were set to evaluate the effects on color display and mechanical properties.
[0168] Pressure range: Test the pressure range displayed in blue and red, low pressure range (0.01-1kPa), high pressure range (1-100kPa).
[0169] Color recovery time: The time it takes for the color to return from the displayed state to the transparent state after the applied pressure is released.
[0170] Low-light contrast ratio: The color display clarity (percentage) in low-light environments.
[0171] Durability: Integrity after multiple cycles of pressure loading, number of test cycles.
[0172] Response consistency: The consistency of color display during multiple pressure loading processes.
[0173] The following table shows the formula of the 6 selected samples:
[0174]
[0175] The following table shows the preparation process of the 6 selected samples:
[0176]
[0177]
[0178] The following table is a summary of the tests on the 6 selected samples:
[0179]
[0180] Test results analysis
[0181] Low-light contrast: T4 achieved the highest contrast of 87%, indicating that the tape can better adapt to low-light environments after improving the optical design.
[0182] Color recovery time: The recovery time of the experimental group was all within 6 seconds, especially T1 and T4, the recovery time was only 4 seconds, indicating the optimization of response speed.
[0183] Durability: The durability of the experimental group (2000-3000 cycles) indicates that the experimental group design has higher performance stability after multiple uses.
[0184] Response consistency: The response consistency of the experimental group was between 94% and 99%, indicating that the particle distribution uniformity and material interface stability were significantly improved.
[0185] Here are three ways to apply it:
[0186] 1: Medical field – Neonatal pressure monitoring
[0187] In neonatal care, the pressure on the baby's skin (such as the contact pressure of a medical fixation belt or a sensing device) needs to be monitored in real time to avoid skin damage.
[0188] Low pressure monitoring: If the tape shows blue, it means the pressure is in a safe range (<1kPa).
[0189] High pressure alarm: If it displays red, it means that the pressure exceeds the safety threshold (>1kPa) and the fixed equipment needs to be adjusted immediately.
[0190] Advantages:
[0191] Instant color display requires no additional power or equipment support.
[0192] The dual color display is intuitive and easy to read, allowing caregivers to make adjustments quickly.
[0193] The transparent state does not affect the observation of skin conditions.
[0194] 2: Logistics field – packaging pressure monitoring
[0195] During the logistics transportation process, the goods need to be packed evenly to avoid damage or loosening of the goods due to excessive or insufficient pressure.
[0196] Pressure monitoring:
[0197] Blue display: Indicates that the cargo is under appropriate protective pressure.
[0198] Red display: Indicates that the packaging pressure is too high, which may cause squeezing damage to the goods.
[0199] No color display: Insufficient pressure, the cargo may have become loose during transportation.
[0200] Advantages:
[0201] Monitor cargo pressure status in real time to reduce breakage rate.
[0202] Easy to use, no additional equipment is required to judge packaging quality.
[0203] The tape is thin, lightweight and low-cost, making it suitable for transport monitoring of bulk goods.
[0204] 3: During surgery, excessive instrument pressure may cause damage to patient tissue, while uneven pressure will affect surgical precision.
[0205] Low-pressure operation (blue display): When the surgeon applies appropriate force, the tape displays blue, indicating that the operation force is moderate.
[0206] High-pressure operation (red display): If the display is red, it reminds the doctor that the force is too great and the pressure needs to be reduced.
[0207] Precise feedback: Doctors can adjust the strength at any time through color changes to ensure safe and accurate operation.
[0208] Tape function:
[0209] Real-time pressure monitoring is achieved to protect patient tissue from excessive pressure damage.
[0210] Provides intuitive feedback to help doctors optimize surgical operations.
[0211] 4. Sports training – intelligent sports trajectory monitoring
[0212] In sports training, by monitoring the force distribution of sports equipment, the movement posture can be optimized and the training effect can be improved.
[0213] Working process:
[0214] Attach pressure-sensitive tape to exercise equipment (e.g., dumbbell grips, barbell bars).
[0215] Low pressure display (blue): When the athlete's grip is even, it displays blue, indicating a normal exercise posture.
[0216] High pressure display (red): If a part displays red, it means that the force is too great, which may be due to improper posture or muscle imbalance.
[0217] Real-time feedback: Coaches or athletes can quickly adjust training movements to avoid injuries by observing the color changes of the tape.
[0218] Advantages:
[0219] Color display does not require electronic equipment support and is real-time and intuitive.
[0220] Can be easily mounted on a variety of sports equipment for easy training feedback.
[0221] The tape is reusable, economical and practical.
[0222] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A dual color display pressure-sensitive tape, comprising a bottom layer, a pressure-sensitive functional layer and a surface layer, characterized in that: The bottom layer is a flexible substrate, which is composed of a polyethylene terephthalate substrate and a flexible material. The polyethylene terephthalate substrate has a thickness of 25-125 μm, and the flexible material is selected from polydimethylsiloxane or thermoplastic polyurethane, with a coating thickness of 30-100 μm, and is used to provide flexible support and fit; The pressure-sensitive functional layer is composed of an elastomer matrix, piezoelectric crystal particles, rare earth oxide particles, conductive fillers, dispersants and cross-linking agents; wherein: The mass proportion of piezoelectric crystal particles is 20%-50%, and they are selected from barium titanate or sodium potassium niobate, which can induce light scattering effect through pressure and display the first color in the low pressure range; The mass proportion of the rare earth oxide particles is 5%-15%, and they are selected from neodymium oxide or europium oxide, and can induce the shift of the light absorption peak by pressure, and display a second color in the high pressure range; The conductive filler accounts for 1% to 5% by mass and is selected from graphene oxide or carbon nanotubes to enhance pressure transmission and response; The mass proportion of the dispersant is 0.5%-2%, and it is selected from polyethylene glycol, polymethyl methacrylate or nonylphenol polyoxyethylene ether, and is used to improve the dispersion uniformity of the particles in the matrix; The cross-linking agent accounts for 1% to 3% by weight and is selected from diisocyanate or peroxide, and is used to enhance the mechanical strength and stability of the base material; The mass proportion of the elastomer matrix is 30%-70%, and is selected from polydimethylsiloxane or polyurethane; The surface layer is an optical enhancement layer, which is made of transparent polycarbonate or polymethyl methacrylate, has a thickness of 10-50 μm, and is coated with a silicon oxide anti-reflective coating to enhance the optical display effect and protect the pressure-sensitive functional layer.
2. The dual color display pressure sensitive tape according to claim 1, characterized in that: The pressure-sensitive functional layer exhibits a bistable optical property within a pressure sensing range, wherein the response pressure of the first color is 0.01-1 kPa, and the response pressure of the second color is 1-100 kPa.
3. The dual color display pressure sensitive tape according to claim 1, characterized in that: The piezoelectric crystal particles and the rare earth oxide particles of the pressure-sensitive functional layer are mixed in a mass ratio of 3:1 to 5:1 to optimize the color conversion effects of low pressure and high pressure.
4. The dual color display pressure sensitive tape according to claim 1, characterized in that: After the pressure is released, the pressure-sensitive functional layer of the adhesive tape can restore the dual-color display to a transparent effect of a pressure-free state within 5 seconds.
5. A method for preparing the dual color display pressure sensitive tape according to claim 1, characterized in that: The following steps are involved: Step 1. Base layer preparation: a. Dissolve polydimethylsiloxane or thermoplastic polyurethane in a matrix material to solvent mass ratio of 1:2 to 1:4, stirring at a speed of 200-500rpm for 20-40 minutes; b. The solution is coated on a polyethylene terephthalate substrate using a blade coating or spin coating process, with a coating thickness of 30-100 μm; c. Curing at 80-120°C for 20-40 minutes to form a flexible bottom layer; Step 2. Preparation of pressure-sensitive functional layer: a. adding piezoelectric crystal particles, rare earth oxide particles, conductive fillers and dispersants to the elastomer matrix material; b. Stirring using a high-speed shear dispersion device at a stirring speed of 3000-5000rpm for 30-60 minutes, and performing ultrasonic dispersion at an ultrasonic frequency of 20-40kHz for 10-20 minutes; c. Add a crosslinking agent and stir at 50-70°C for 60-90 minutes to form a uniform pressure-sensitive functional material; d. Use roller coating or spray coating process to apply on the base layer with a coating thickness of 50-150μm; e. Curing at 120-150°C for 30-60 minutes to form a pressure-sensitive functional layer; Step 3. Surface preparation: a. Using an extrusion molding process to make a transparent polycarbonate or polymethyl methacrylate film with a thickness of 10-50μm; b. Spraying a silicon oxide anti-reflective coating on the surface of the film with a coating thickness of 50-200nm; c. Curing at 120-180°C for 5-15 minutes to form an optical enhancement layer; Step 4. Multi-layer composite: a. Arrange in the order of bottom layer, pressure-sensitive functional layer and surface layer; b. Use vacuum hot pressing process for multi-layer composite, the hot pressing temperature is 80-120℃, the pressure is 30-100MPa, and the time is 20-40 minutes; Step 5. Cutting and shaping: a. Use laser cutting equipment to cut to the predetermined size, the laser power is 15-30W, and the cutting speed is 5-20mm / s; b. Trim the edges to ensure they are smooth and free of burrs.
6. The preparation method according to claim 5, characterized in that: In the operation steps of the vacuum hot pressing process, the bottom layer and the surface layer are electrostatically cleaned before composite lamination to remove surface particles and improve composite quality.
7. The preparation method according to claim 6, characterized in that: The dispersant is added in two steps: the first step is to add 50% of the dispersant before high-speed shear dispersion, and the second step is to add the remaining 50% of the dispersant before ultrasonic dispersion to further improve the dispersion uniformity of the particles.